Selected Mechanisms of Action of Bacteriophages in Bacterial Infections in Animals - Renata Urban-Chmiel; Ewelina Pyzik (Viruses)
Bacteriophages, as ubiquitous bacterial viruses in various natural ecosystems, play an important role in maintaining the homeostasis of the natural microbiota. For many years, bacteriophages were not believed to act on eukaryotic cells; however, recent studies have confirmed their ability to affect eukaryotic cells and interact with the host immune system. Due to their complex protein structure, phages can also directly or indirectly modulate immune processes, including innate immunity, by modulating phagocytosis and cytokine reactions, as well as acquired immunity, by producing antibodies and activating effector cells. They can therefore have a profound impact on the course of bacterial infections by stimulating and at the same time inhibiting the systemic pro-inflammatory response. This review article presents a characterization of the processes by which bacteriophages affect selected immune mechanisms in selected animal species. The results of our own experiments using calves are also presented as examples. The paper contains many new examples of potential uses of bacteriophages and their effects on eukaryotic cells, especially in the course of bacterial infections, which are extremely important in experimental treatments exploiting phages as alternatives to antibiotics. The positive results of the effects of bacteriophages on eukaryotic cells during infections open up promising new prospects for their use as natural tools in the treatment of bacterial, fungal, and viral diseases in animals and humans.